1997
DOI: 10.1002/(sici)1097-0282(199707)42:1<89::aid-bip8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Tapping mode atomic force microscopy of scleroglucan networks

Abstract: Tapping mode Atomic Force Microscopy (TmAFM) has been used to study the fungal polysaccharide scleroglucan deposited from aqueous solution and dimethyl sulfoxide (DMSO) onto a mica surface. The solutions from which the microscope samples were produced were prepared by first dissolving the solid scleroglucan in 0.1M NaOH, then neutralizing the solution with HCl, followed by dilution to the required concentration in either water or DMSO. It was found that from the aqueous solution described above, scleroglucan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Scleroglucan has been shown to exhibit strand heights of 0.8 ± 0.5 nm for the native triple-helical form [16]. The difference in these numbers is thought to be due to flattening and spreading of the biopolymer on the surface during the drying process [17,18].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Scleroglucan has been shown to exhibit strand heights of 0.8 ± 0.5 nm for the native triple-helical form [16]. The difference in these numbers is thought to be due to flattening and spreading of the biopolymer on the surface during the drying process [17,18].…”
Section: Resultsmentioning
confidence: 98%
“…End to end association of the helices must therefore occur when the dilute solutions of laminarin are dried onto mica as the observed helices are considerably longer than the 12.5 nm contour length. Linking of helices has previously been observed in polysaccharide systems [12,17,21,22]. This indicates that the structures are formed from end associated helices or microfibrils.…”
Section: Resultsmentioning
confidence: 99%
“…6 C) or at NaOH concentrations above 0.1 N (data not shown). ␤-(1,3)-glucan microfibrils have been described in the literature as associations of triple helices which held together (Cheeseman & Brown, 1995;Gawronski et al, 1999;McIntire & Brant, 1997;Vuppu, Garcia, & Vernia, 1997). As temperature increased under alkaline environment, disappearance of microfibrils could be related to the increase in single strands proportion and the simultaneous decline or disappearance of triple helical conformation.…”
Section: Transmission Electron Microscopy (Tem) Of Treated Epsmentioning
confidence: 99%
“…Vuppu et al reported on the rod-like structure of ␤-(1,3)(1,6)-glucan, scleroglucan, by tapping mode atomic force microscopy. 8 Previously, we have clarified from the static light scattering (SLS) measurements for curdlan solutions in various concentrations of NaOH that the curdlan molecules associate at 25°C, and the molecular associations dissociate at 60°C. 9 We have reported that a decrease in the concentrations of NaOH promotes the molecular association.…”
Section: Introductionmentioning
confidence: 99%